FAKTOR RISIKO GANGGUAN PSIKOLOGIS PADA IBU POSTPARTUM DI RSUD KOTA BEKASI - vivi dwi putri (Masker Medika, 2022)
Postpartum mood disorder is not a trivial issue. It has possibility to disrupt the life of the mother, family, baby and other children. Mother will have difficulty in caring and maintaining adequate emotional bond to the baby and other children. To study and analyze The Risk Factors of Psychological Disorders on Postpartum Mothers in Bekasi City Hospital at 2015. This research is an analytic research with cross sectional approach. Data collection was done on February 26, 2015. The population in this research are all mothers who gave birth in Bekasi City Hospital with a total sample of 155 mothers. Sample technique is accidental sampling. The results of research shows that psychological disorders on postpartum mothers relates with education factor (p value = 0.011), parity (p value = 0.011), giving birth types (p value = 0.007), social support (p value = 0.004), and not related, they are age factor (p value = 0.068) and work status (p value = 0.125). And the most dominant factor is social support with OR score = 3.782. It is expected that hospitals can giving directions to health workers replace the roles of a husband and family the mothers postpartum that is less social the provision of support of them.